2014
DOI: 10.1186/1472-6963-14-373
|View full text |Cite
|
Sign up to set email alerts
|

Research capacity and training needs for non-communicable diseases in the public health arena in Turkey

Abstract: BackgroundThe aim of this study is to define the research capacity and training needs for professionals working on non-communicable diseases (NCDs) in the public health arena in Turkey.MethodsThis study was part of a comparative cross-national research capacity-building project taking place across Turkey and the Mediterranean Middle East (RESCAP-Med, funded by the EU). Identification of research capacity and training needs took place in three stages. The first stage involved mapping health institutions engaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
(25 reference statements)
2
28
0
Order By: Relevance
“…However, HRSCS remains one of the world's unmet challenges in developing countries [20] in particular in the context of the 10/90 gap; that less than 10% of global resources for HR addressed health problems in developing countries, where over 90% of preventable deaths occurred [21]. The 10/90 gap, has essentially remained the same nearly three decades after the gap was first identified, has significant consequences; not only is HRSC not strengthened in low-resources countries, but there are, as a result, relatively relevant findings of major gaps in HRSC can also be applied to policy processes, clinical practices, and monitoring and evaluation of research results and outputs generally and in sub-Saharan Africa [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HRSCS remains one of the world's unmet challenges in developing countries [20] in particular in the context of the 10/90 gap; that less than 10% of global resources for HR addressed health problems in developing countries, where over 90% of preventable deaths occurred [21]. The 10/90 gap, has essentially remained the same nearly three decades after the gap was first identified, has significant consequences; not only is HRSC not strengthened in low-resources countries, but there are, as a result, relatively relevant findings of major gaps in HRSC can also be applied to policy processes, clinical practices, and monitoring and evaluation of research results and outputs generally and in sub-Saharan Africa [22].…”
Section: Introductionmentioning
confidence: 99%
“…Across the Middle East and North Africa (MENA) region, HR faces critical deficits in governance, resources, and capacity in terms of knowledge production, dissemination, and application [11,22].…”
Section: Introductionmentioning
confidence: 99%
“…While RESCAP-MED had identified the range of disciplines and fields to cover in training workshops, we devised a training needs assessment (TNA) for partners to extend their knowledge of perceived gaps and training needs within their countries. TNA were completed in Jordan, Lebanon, Palestine, Tunisia, and Turkey (see [43] for Turkish analysis and overall design of TNA). Syrian counterparts completed the first phase of the TNA, the mapping of health institutions, but were forced to discontinue the remaining phases as the political and security situation in Syria deteriorated in 2012.…”
Section: Results: Examining Achievementsmentioning
confidence: 99%
“…This scene not only hampers any HR development effort but also threatens the continuity of public services, particularly education and health. Furthermore and as another study revealed, in view of capacity gaps, building a robust HRS will be unattainable as long as we lack a governing framework, strategic thinking in resources and capacity allocation, and sustainable investment for HR (4,21,33). In recent years, a growing number of projects have supported the Palestinian HR capacity through international and local parties, for instance, European Union-Horizon 2020, academic partnerships, UN agencies, the Islamic Development Bank, governments (such as Palestinian-French joint committee, the Palestinian-German Science Bridge, Palestine-Quebec Science Bridge, the Norwegian Institute of Public Health through Norway's Minister of Foreign Affairs, and others), Qatar Charity, Welfare Association, and local private sector (including banks, pharmaceuticals companies, and businessmen).…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, HR across the Middle East and North Africa region faces critical deficits, most notably are governance, resources, and capacity of the knowledge production and application (4,21). Similar deficits exist in Palestine with insufficient understandings and conceptualizations about the reality of HR potentials.…”
Section: Introductionmentioning
confidence: 99%